On the Categories of Institutional Discourse in Linguistics - Islamjanova, Khazifakhan; Annazarova, Tamilla Dilshod qizi (The Lingua Spectrum, 2026)
This article provides a systematic analysis of the concept of institutional discourse in modern linguistics, describing its theoretical foundations, essential features, and the categories that determine its structure and functioning. The study reviews leading scholarly views, conceptual approaches, and methodological principles, and summarizes previous research through comparative, descriptive, and analytical methods. Particular attention is paid to the influence of social status, institutional roles, and communicative intentions of participants, which shape discourse strategies, tactics, and patterns of interaction. The paper emphasizes the significance of extra-linguistic factors, including social, cultural, psychological, and pragmatic aspects, in the production and interpretation of institutional communication. It demonstrates how linguistic units operate together with contextual conditions to form stable genres and recurring communicative models. The results clarify the structural and functional characteristics of institutional discourse, develop a typology of its genres and types, and provide theoretical generalizations and practical recommendations. The research offers an interdisciplinary framework that can serve as a reliable basis for further linguistic and discourse studies.